Designing an effective eco-economic integration mechanism for sectoral projects within a diversified investment program - Chupryna , Iu.; Tormosov , R.; Predun , K. (Ways to Improve Construction Efficiency, 2023)
This article addresses the development of an effective mechanism for eco-economic integration of sectoral projects into a diversified investment program. The focus is placed on the necessity of combining environmental responsibility with economic feasibility in forming an investment portfolio under conditions of dynamic changes in resource availability, regulatory frameworks, and global sustainable development challenges. In the context of decentralization, digitalization of governance, and the energy transition, the role of environmentally oriented approaches to structuring investment programs is growing—programs that incorporate projects from various sectors, ranging from construction to industry and energy. The study proposes a conceptual model of a mechanism that synchronizes environmental, economic, and managerial criteria using advanced analytical tools (BI, ESG monitoring, LCA analysis). This enables not only the evaluation of each project’s potential but also the construction of integrated programs that account for the interaction between portfolio components. The paper outlines four stages of implementing such a mechanism: diagnostics of sectoral projects, integration of environmental KPIs into the investment evaluation system, multi-criteria selection considering risk factors, and program balance management through digital control panels. A matrix structure is proposed for analyzing the synergy between the environmental impacts of projects and their economic performance, which helps to avoid goal conflicts and improve the overall efficiency of the investment program. The fundamental principles for constructing the mechanism are identified: scientific validity, adaptability, transparency, multi-sectoral applicability, and digital validation. The novelty lies in combining ecological and financial modeling within a unified decision-making platform. The results of the research may be applied by public administration bodies, institutional investors, international donors, and corporations implementing sustainability strategies within portfolio-based planning frameworks.